Pour une approche organologique de la littérature - Simon Woillet (Appareil)
This article aims at establishing a method of comparative reading of Stendhal’s autobiographical texts and the so-called “psychotic” writings, which inspired the writers of the ideophonographic avant-gardes of the 20th century (from Surrealism to Dadaism via Lettrism). To support this comparison, we explore the material causes of this type of literary innovation (notably the industrial development of the poster), while adopting an “organological” and psychoanalytic approach of the literature. This approach is interested in the symbolic role given by the writing subject to the technical objects which serve as mediations to formulate his desires, anxieties and fantasies, as well as to objectify his psychic contradictions through written materialization. The liberation of the visual potential of writing appears in these two types of literature as the condition of possibility for a semiotic renewal of literary and artistic modernity.